The Role of Arabic Language Learning Method and Its Relevance for Future Arabic Teachers: Ernest Nagel's Perspective - Muhammad Fadli Ramadhan; Suhayib; Abd Rofi Fathoni Nidhomillah; Nikmatul Makfiro (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2024)
This research explores the relevance of this course for future Arabic teachers through the lens of Ernest Nagel's theory, which emphasizes the integration of theory, methodology, and practice. Data was gathered through interviews with course instructors. The findings reveal that the lecturer employs a structured teaching approach that incorporates Nagel's principles, offering students both theoretical insights and practical experience. Students are trained to develop interactive teaching strategies using current technology, preparing them to teach effectively in digital learning environments. This hands-on approach enhances their teaching skills and aligns with modern educational needs. The research suggests that this integrated model could serve as a valuable framework for Arabic language education programs, highlighting the importance of combining theory with practice to effectively prepare future educators